Tarhamustikka Pohjois-Suomessa vain harrastuskasvi - Hoppula, Kalle; Hoppula, Kati; Tahvonen, Risto; Järvelin, Vesa; Ylijoki, Janne; Soppela, Kaisa; Luoma, Sirkka; Kekkonen, Hanna (Suomen maataloustieteellinen seura, 2012)
V ok